Non Compliance Pattern of Anti Hypertensive Treatment - Nabi, Golam; Boral, Paritosh Kumar; Mohanta, Debeshis; Mou, Farah Tasneem; Rokonuzzaman, SM (Journal of Dhaka Medical College, 2016)
A cross-sectional type of observational study was conducted on hypertensive patients attending at medicine department (OPD and admitted) of Z. H. Sikder Womens Medical College Hospital, Dhaka, from January to June 2014, to see the patient compliance of anti-hypertensive drugs. The sample size was 185. Patients with evidence of hypertension as per Seventh Joint National Committee Criteria (defined as systolic blood pressure >140 mm oh Hg or diastolic blood pressure >90 mm of Hg or use any anti-hypertensive medication, regardless of blood pressure. Time from initiation of antihypertensive treatment was at least 3 months and patients between 18-70 years were included in this study. A pre-tested questionnaire was used to gather sociodemographical and relevant epidemiological data. Standard blood pressure measurement was recorded as the average of 2 measurements to detect anti-hypertension. Patients were asked for their reasons of noncompliance, knowledge regarding importance of compliance, side effects of drugs and family support. Mean age of the patients was 47.40(±5.09) years. 75.9% of the non adherent population is in the 41-50 years age group. 85% percent of the patients were found non-adherent to treatment. Out of 158 non adherent population, 54.43% were male and 45.57% were female. 38.6% of the non-adherent people have no education or a primary education, only 7.6% were graduate and above. 42.41% of the non-adherent people were poor and earning < 5000 taka/month. Majority duration of disease ranged from 1 to 15 years which was 50%, with an average of 3.99(±3.47) years. The most commonly prescribed antihypertensive medicine was beta blockers. 49.4% of the non-adherent population was advised to take relatively costly antihypertensive drug (Calcium channel blocker, ACEI, ARB). The main reason for not taking the medication was forgetfulness (48.1%) and the economic reason for non-compliance was only 7.59%. About 63% patients felt hypertension is not a curable disease, 42% 0f the study subjects were not sure about the signs and symptoms of HTN and another 30.6% said that HTN had no definite sign symptom.77.4% of the respondent said that preservation of previous prescription is important to understand HTN status. The overall Knowledge on complication of uncontrolled hypertension of the adherent people was relatively higher than that of nonadherent people. 96.4% of the adherent people knew that uncontrolled hypertension can cause brain stroke, whereas only 81.65% of the non-adherent people knew that. Most of the respondent of the both adherent and non-adherent group informed that hypotension, severe weakness, anorexia, nausea and impotency were the important side effect of antihypertensive drugs. Most of the (87.5%) participant went for follow up when they felt hypertensive, 35% change medicine for expenses and 27% stop taking drug when BP is under control. 78% did not know whether only regular anti-hypertensive can prevent complication or not, 62% of the respondent did not think that to buy drug is wastage of money. One-third of the respondent said that they were never asked to take medicines or visit physician by their family members. And half of the respondents had to depend on monetary support of the family member for treatment. 99.36% of non-adherent missed their follow up. J Dhaka Medical College, Vol. 24, No.2, October, 2015, Page 108-116